Pembuatan Aplikasi Mobile Augmentative and Alternative Communication "BerKata" dengan Menggunakan Text to Speech untuk Membantu Komunikasi Anak Penyandang Autisme - Evandruce Filbert; Rolly Intan; Henry Novianus Palit (Jurnal Infra, 2021)
Children with autism who lack verbal communication skills often confuse their parents for knowing what their wants are conveniently. It takes extra effort for their parents to understand them, especially with their unclear pronunciations. Their inability to conveniently understand what is kept in their minds may affect their emotions. The children easily experience mood swings, and their parents struggle to identify their children’s needs. All of these struggles can be supported with the Augmentative and Alternative Communication (AAC) with Picture Exchange Communication System (PECS) module. With PECS, children with autism will be able to learn how to converse their needs through image media. Therefore, their parents can easily understand what they want to say. With all the problems, this research presents an AAC mobile application with PECS module called “BerKata”. The result of this research is that “BerKata” may develop children with autism’s speech ability, to decrease their anxiousness and help gaining their confidence, if only their parents consistently use it. Keep in mind to achieve the goal, requires consistency of habituation from children, parents and the people around and not an instant result.